Calcium triggers the dissociation of myosin‐Va from ribosomes in ribonucleoprotein complexes. Issue 14 (30th May 2020) - Canclini, Lucía; Cal, Karina; Bardier, Camila; Ruiz, Paul; Mercer, John A.; Calliari, Aldo
Abstract : The sorting of RNAs to specific regions of the cell for local translation represents an important mechanism directing protein distribution and cell compartmentalization. While significant progress has been made in understanding the mechanisms underlying the transport and localization of mRNAs, the mechanisms governing ribosome mobilization are less well understood. Ribosomes present in the cytoplasm of multiple cell types can form ribonucleoprotein complexes that also contain myosin‐Va (Myo5a), a processive, actin‐dependent molecular motor. Here, we report that Myo5a can be disassociated from ribosomes when ribonucleoprotein complexes are exposed to calcium, both in vitro and in vivo . We suggest that Myo5a may act as a molecular switch able to anchor or release ribosomes from the actin cytoskeleton in response to intracellular signaling. Abstract :